Hypoxia induces alterations in tRNA modifications involved in translational control - Guo, Huanping; Xia, Lin; Wang, Wei; Xu, Wei; Shen, Xipeng; Wu, Xiao; He, Tong; Jiang, Xuelin; Xu, Yinying; Zhao, Pan; Tan, Dongmei; Zhang, Xi; et al. (BMC biology, 2023)
Adaptation to high-altitude hypobaric hypoxia has been shown to require a set of physiological traits enabled by an associated set of genetic modifications, as well as transcriptome regulation. These lead to both lifetime adaptation of individuals to hypoxia at high altitudes and generational evolution of populations as seen for instance in those of Tibet. Additionally, RNA modifications, which are sensitive to environmental exposure, have been shown to play pivotal biological roles in maintaining the physiological functions of organs. However, the dynamic RNA modification landscape and related molecular mechanisms in mouse tissues under hypobaric hypoxia exposure remain to be fully understood. Here, we explore the tissue-specific distribution pattern of multiple RNA modifications across mouse tissues. By applying an LC-MS/MS-dependent RNA modification detection platform, we identified the distribution of multiple RNA modifications in total RNA, tRNA-enriched fragments, and 17-50-nt sncRNAs across mouse tissues; these patterns were associated with the expression levels of RNA modification modifiers in different tissues. Moreover, the tissue-specific abundance of RNA modifications was sensitively altered across different RNA groups in a simulated high-altitude (over 5500 m) hypobaric hypoxia mouse model with the activation of the hypoxia response in mouse peripheral blood and multiple tissues. RNase digestion experiments revealed that the alteration of RNA modification abundance under hypoxia exposure impacted the molecular stability of tissue total tRNA-enriched fragments and isolated individual tRNAs, such as tRNA , tRNA , tRNA , and tRNA . In vitro transfection experiments showed that the transfection of testis total tRNA-enriched fragments from the hypoxia group into GC-2spd cells attenuated the cell proliferation rate and led to a reduction in overall nascent protein synthesis in cells. Our results reveal that the abundance of RNA modifications for different classes of RNAs under physiological conditions is tissue-specific and responds to hypobaric hypoxia exposure in a tissue-specific manner. Mechanistically, the dysregulation of tRNA modifications under hypobaric hypoxia attenuated the cell proliferation rate, facilitated the sensitivity of tRNA to RNases, and led to a reduction in overall nascent protein synthesis, suggesting an active role of tRNA epitranscriptome alteration in the adaptive response to environmental hypoxia exposure.